Computation with Energy-Time Trade-Offs: Models, Algorithms and Lower-Bounds - Bingham, B.D.; Greenstreet, M.R. (2008 IEEE International Symposium on Parallel and Distributed Processing with Applications, 2008)
Power consumption has become one of the most critical concerns for processor design. This motivates designing algorithms for minimum execution time subject to energy constraints. We propose simple models for analysing algorithms that reflect the energy-time trade-offs of CMOS circuits. Using these models, we derive lower bounds for the energy-constrained execution time of sorting, addition and multiplication, and we present algorithms that meet these bounds. We show that minimizing time under energy constraints is not the same as minimizing operation count or computation depth.